The Structure of Bacteriological, Virological and Immunology Laboratories. Groups of Micro-Organisms. Simple Painting Techniques. - Tuyg’unovna, Shukurova Shoxina (American Journal of Botany and Bioengineering, 2024)
This article contains the necessary information about the structure of bacteriological, virological and immunological laboratories, groups of microorganisms, and simple staining methods. You can learn about several types of microscopes for microbiological examinations (biological, fluorescent, electron) and special methods and devices for viewing in a microscope (space-contrast, darkfield).